Pentacentrus rectangulus sp. nov., the twelfth Pentacentrus species recorded in China (Orthoptera: Gryllidae; Pentacentrinae) - Dai, Jin-Hong; Xie, Can-Hong; Ma, Li-Bin (Zootaxa, 2024)
Pentacentrus rectangulus sp. nov. is the twelfth Pentacentrus species we have found in China. This new species has a uniformly colored head (without longitudinal yellow stripe on the occiput, and the color of the scape and peduncle segments is the same as that of the first three flagellar segments), and significantly curved ectoparamere. It has a similar coloration (coloration of the forewings and hind feet) to that of both Pentacentrus bituberus Liu & Shi, 2011 and Pentacentrus medogensis Zong, Qiu & Liu, 2017, but the morphology of the male genitalia differs markedly (the ventral inner margin of the epiphallus of the new has tufts of bristles, which is not present in either P. bituberus or P. medogensis). Here, we describe and illustrate the new species, and we also provide a key to the Chinese species of the genus.